A Byzantine Lead Seal from Paphlagonian Hadrianopolis - Kasım Oyarçin; Ersin Çelikbaş (Art-Sanat)
The subject of this article is a Byzantine lead seal found during the excavations of the Inner Castle Baptistery of Paphlagonian Hadrianopolis in 2022. The lead seal found during the archaeological excavations in the baptistery is understood to belong to the 11th century AD thanks to the coins found in the same layer with the seal. The dotted borders on the obverse and reverse are carved very close to each other, and the borders became straight lines in some places. On the obverse of the seal, Archangel Michael is depicted within a dotted border, wearing an outfit decorated with precious stones, with diademed curly hair, holding a scepter in his right hand and a globus in his left hand. The reverse reads an address in four lines within a dotted border, the first line beginning with a cross. These kinds of seals are categorized by sigillographers as private seals used for personal business since they do not bear the owner’s title or position on the reverse, except for his name. An evaluation of the Byzantine lead seal together with the coins found in the same context revealed that it has a significant place in terms of indicating that Hadrianopolis continued to be inhabited until the 11th-12th century AD, albeit on a small scale, which was previously considered to have been abandoned due to the interruption of data from archaeological excavations starting from the middle of the 7th century AD.